2023
DOI: 10.1001/jamacardio.2022.4457
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Clinical Trial Sites for Novel Transcatheter Mitral and Tricuspid Valvular Therapies

Abstract: ImportanceRacial and ethnic minority and socioeconomically disadvantaged patients have been underrepresented in randomized clinical trials. Efforts have focused on enhancing inclusion of minority groups at sites participating at clinical trials; however, there may be differences in the patient populations of the sites that participate in clinical trials.ObjectiveTo identify any differences in the racial, ethnic, and socioeconomic composition of patient populations among candidate sites in the US that did vs di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…However, prior research from our group has shown that diverse site selection alone may not sufficiently improve racial and ethnic diversity among clinical trial populations, given the similar racial and ethnic demographics of patients served by US clinical trial sites for novel transcatheter mitral and tricuspid valve therapies vs sites not conducting clinical trials . Thus, US hospitals involved in clinical trials must actively engage their Black and Hispanic communities to improve enrollment in clinical trials . Future efforts may benefit from focusing on social determinants of health, such as improving access to transportation and childcare services for Black and Hispanic patients, who may be limited in participating in trials by an inability to leave work and/or find care for children and other dependents during multiple study visits …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, prior research from our group has shown that diverse site selection alone may not sufficiently improve racial and ethnic diversity among clinical trial populations, given the similar racial and ethnic demographics of patients served by US clinical trial sites for novel transcatheter mitral and tricuspid valve therapies vs sites not conducting clinical trials . Thus, US hospitals involved in clinical trials must actively engage their Black and Hispanic communities to improve enrollment in clinical trials . Future efforts may benefit from focusing on social determinants of health, such as improving access to transportation and childcare services for Black and Hispanic patients, who may be limited in participating in trials by an inability to leave work and/or find care for children and other dependents during multiple study visits …”
Section: Discussionmentioning
confidence: 99%
“…There are currently limited data on the enrollment of socioeconomically disadvantaged populations in clinical trials. Prior work from our group has shown that sites that participate in clinical trials for VHD care for patients who are wealthier and have higher levels of socioeconomic status than candidate hospitals that do not . Increased access for these patients may be spurred by a priori decision-making at site selection for clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Nathan et al sought to shine light on the degree to which the characteristics of patients undergoing transcatheter mitral and tricuspid valve surgery differ between hospitals that do and do not participate in clinical trials of transcatheter mitral and tricuspid valve procedures. The researchers found that the racial and ethnic makeup of patients undergoing cardiac surgery in hospitals that participated in clinical trials vs those that did not was similar.…”
mentioning
confidence: 99%
“…Unfortunately, disparities in the socioeconomic status of persons participating in large cardiovascular outcomes trials are harder to quantify, as socioeconomic indicators are not routinely collected. In contrast to what was seen for race and ethnicity, Nathan et al found that hospitals that did not participate in clinical trials did care for more socioeconomically disadvantaged patients. This highlights the need to improve support for clinical trials in health systems that care for a greater number of socioeconomically disadvantaged persons.…”
mentioning
confidence: 99%
See 1 more Smart Citation